PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN TAMALATEA KABUPATEN JENEPONTO - Putri Alfiana Tinggi; Muh. Ichwan Musa; Burhanuddin; Agung Widhi Kurniawan; Uhud Darmawan Natsir (Lafadz Jaya Publisher, 2023)
This research aims are to (1) find out how the influence leadership style on employee performance, (2) knowing how to influence motivation on employee performance, (3) knowing how style influences leadership and work motivation on employee performance in the Office Tamalatea District, Jeneponto Regency. Data used in this research is primary and secondary data with a total sample of 40 respondent. This study uses a quantitative approach and analysis using the method of multiple linear regression analysis with the help of the data SPSS 25 to prove three hypotheses. The results of this study prove that Leadership Style has a significant effect on performance employee t value arithmetic leadership style variable of -3.030 < t table of 1,687. That the t count of the motivational variable is 5,606 > the t table is 3,252. simultaneously variable leadership style and work motivation on employee performance with F count of 15,942 this shows F count (15,942) > F table (3.252). Based on the results of this study it is also known that the independent variable simultaneously or simultaneously have a significant effect on variables dependent, namely Work Motivation at the Tamalatea district office jeneponto. Therefore, if employee performance continues to be considered and improved then of course it will improve employee performance moreoptimal.